Chimeric Antigen Receptor T Cell Immunotherapy for Tumor: A Review of Patent Literatures - Fu, Manxue; Tang, Liling (Recent Patents on Anti-Cancer Drug Discovery, 2019)
Background: Chimeric Antigen Receptor (CAR) T cell immunotherapy, as an innovative method for tumor immunotherapy, acquires unprecedented clinical outcomes. Genetic modification not only provides T cells with the antigen-binding function but also endows T cells with better immunological functions both in solid and hematological cancer. However, the CAR T cell therapy is not perfect because of several reasons, such as tumor immune microenvironment, and autologous limiting factors of CAR T cells. Moreover, the safety of CAR T cells should be improved. Objective: Recently many patents and publications have reported the importance of CAR T cell immunotherapy. Based on the patents about CAR T cell immunotherapy, we conclude some methods for designing the CAR which can provide information to readers. Methods: In this review, we collect recent patents and publications, summarize some specific antigens for oncotherapy from patents and enumerate some approaches to conquering immunosuppression and reinforcing the immune response of CAR T cells. We also sum up some strategies for improving the safety of CAR T cell immunotherapy. Results: CAR T cell immunotherapy as a neotype cellular immunotherapy has been proved effective in oncotherapy and authorized by FDA. Improvements in CAR designing enhance functions of CAR T cells. Conclusion: This review, summarizing antigens and approaches to overcome defects of CAR T cell immunotherapy from patents and publications, might contribute to a broad readership.
Keywords: safety